Retinal characteristics of the congenital disorder of glycosylation PMM2‐CDG. Issue 6 (22nd February 2013) - Thompson, Dorothy A.; Lyons, Ruth J.; Russell‐Eggitt, Isabelle; Liasis, Alki; Jägle, Herbert; Grünewald, Stephanie
Abstract: The congenital disorder of glycosylation, PMM2‐CDG, is associated with progressive photoreceptor degeneration, which causes a pigmentary retinopathy. We identified a sibling pair, mildly affected with PMM2‐CDG, who showed preserved photoreceptor function, but profound deficits of the 'on‐pathway' in the retina. This localises the site of early, or initial, retinal dysfunction in PMM2‐CDG to the synapse in the outer plexiform layer between bipolar cells, photoreceptors and horizontal cells. We sought wider evidence to support this novel finding by reviewing retrospectively the case notes of eight patients, diagnosed with PMM2‐CDG between the ages of 7 months to 16 years. We compared the clinical presentation and electroretinograms, (ERGs), of these patients with the sibling pair. We found that five of eight patients showed characteristic ERG features of on‐pathway dysfunction in the form of reduced ERG b‐wave amplitude. The remaining three patients had significant photoreceptor dysfunction by the time of ERG recording, and both a‐ and b‐wave amplitudes were markedly attenuated. We conclude that ERG signs of on‐pathway dysfunction can be detected in the early stages of PMM2‐CDG. Referral for electroretinography evidence of this specific on‐pathway deficit, with preservation of oscillatory potentials, can help establish the diagnosis of infants with developmental delay or failure to thrive in whom a glycosylation defect is suspected. Also by increasing our understanding of the interaction of N‐glycoproteins at this synapse we may be able to design future therapeutic intervention to prevent or ameliorate the progressive visual loss associated with PMM2‐CDG.